Immaculate forms : a history of the female body in four parts - King, Helen, 1957- (Basic Books, 2025)
"Breasts, clitoris, hymen, and womb. Across history, these body parts have told women who they are and what they should do. Although knowledge of each part has changed through time, none of them tells a simple story. The way they work and in some cases even their existence have been debated. They can be seen as powerful or as disgusting, as relevant only to reproduction or as sources of sexual pleasure. In Immaculate Forms, classicist and historian Helen King explores the symbiotic relationship between religion and medicine and their twinned history of gatekeeping over these key organs that have been used to define "woman," illustrating how conceptions of women's bodies have owed more to imagination and myth than to observation and science"--